Effects of tibolone on the risk factors for cardiovascular diseases in postmenopausal women - Jeremić Katarina; Lazović Gordana; Tulić Ivan; Gojnić Miroslava; Stojnić Jelena; Jeremić Jelena (Vojnosanitetski Pregled)
Background/Aim. Tibolone is a preparation that belongs to the group of steroidal substances. The effects of the use of the use of tibolone are the consequence of the activities of its metabolities, considering that their hormonal activity depends on the type of tissue in which they develop. The aim of this study was to evaluate the influence of the use of tibolone on risk factors for the development of cardiovascular diseases in postmenopausal women. Methods. A prospective observational stady included 94 patients who had the concentration of l7ß estradiol < 50 pg/ml, and who was in menopause more than a year. Out of the total number of patients, 63 accepted to receive tibolone 2.5 mg daily (tibolone group), while 31 of the patients refused to take tibolone (control group). We measured the concentration of lipids (cholesterol, LDL cholesterol, HDL cholesterol, triglicerides), antitrombin III, fibrinogen, and C-reactive protein, before and after the treatment within a 6-month period. Then, we compared the difference between the values of concentrations and tested the statistical significance of the difference. We also evaluated the changes of values in the concentrations of the examinated parameters inside a 6-month period in the control group. Results. In 31 patients of the control group, from the control group there were no significant changes in the values of the defined parameters as compared to their initial values after six months. But there were changes of statistical significance (p < 0.001) in values of the concentrations of the exeminated parameters before and after the treatment in the tibolone group. In fact, we recorded decreases in the total cholesterol by 17.8%, HDL cholesterol by 27%, LDL cholesterol by 4% (without statistical significance p > 0.05) and triglicerids by 35%. There were no statistical differences in the concentrations of antitrombin III, fibrionogen, and C-reactive proteine in the tibolone group before and after the treatment. Conclusion. The use of tibolone dose decrease the concentration of the total cholesterol, triglicerides, HDL cholesterol, without a significant decrease of LDL cholesterol. Also, the use of tibolone does not have any significant effect on the concentrations of antitrombin III, fibrinogen and C-reactive proteine. The number of serum parameters measured in this study was limited, thus that was the reason to discuss only about the metabolism of lipids in the patients from the tibolone group. The final conclusion about the risk for cardiovascular diseases in the patients on tibolone, howerer, reqnires were extensive further clinical exeminations.